Citric Acid Catalyst-Assisted Bioactive Glass with Hydrogen Peroxide for In Vitro Bioactivity and Biodegradability Using Sol-Gel Method - Aklilu, Tsion Chuni; Ewnete, Bethelhem Gashaw; Dachasa, Kena; Sanbaba, Kanate; Tesfaye, Demeke; Wondimu, Tadele Hunde; Kim, Jung Yong; Tulu, Ketema Tafess; Lemma, Shimelis; Ejeta, Balisa Mosisa; Bakare, Fetene Fufa (International Journal of Biomaterials, 2023)
In this study, carbon-free and completely soluble hydrogen peroxide (H2O2) was utilized in place of conventional surfactants as a pore-forming agent. Citric acid was also used in low concentration for the hydrolysis reaction. A sol-gel method was used to prepare bioactive glass (BG) specimens of H2O2-untreated BG, 1M, 2M, and 3M H2O2-treated BGs. X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), energy-dispersive spectroscopy (EDS), and nitrogen adsorption/desorption isotherm with the Brunauer–Emmett–Teller (BET) method were used for analyzing the samples’ phase, surface morphology, chemical composition, constituent composition, pore size, and specific surface area respectively. In vitro bioactivity, as well as biodegradability tests, was performed on samples by immersing them in simulated body fluid (SBF) solution. According to the results, BG particles treated with 2 M H2O2 exhibited higher specific surface area (SSA), which is 189.55 cc/g, and better in vitro bioactivity and biodegradability.